Effects of increasing replacement of dietary fishmeal with plant protein sources on growth performance and body lipid composition of Atlantic salmon (Salmo salar L.) - Pratoomyot, Jarunan; Bendiksen, Eldar Asgard; Bell, J Gordon; Tocher, Douglas R (Aquaculture, 2010)
The effects of high levels of replacement of dietary fish meal (FM) by mixtures of plant protein (PP) sources on growth performance, lipid composition, protein and lipid digestibility and fatty acid profile were investigated in Atlantic salmon, Salmo salar. Experimental diets containing 35% protein and 28% lipid were formulated with a low level of FM that was replaced by increasing levels of PP resulting in four diets of 25/45 ((% FM/% PP, F25), 18/50 (F18) 11/55 (F11) and 5/60 (F5). Dietary oil was supplied by a fish oil (FO) and rapeseed oil blend at a ratio of ~40/60 so this formulation was effectively a dual replacement of FO and FM. Diets were supplemented with crystalline amino acids, to compensate for the reduction in indispensible amino acids due to reduced FM content, and all diets were supplemented with lecithin. Salmon, initial weight 1.30 ± 0.1 kg, were fed one of the four experimental diets for 19 weeks. Feed consumption decreased as PP inclusion in diets increased, probably as a result of reduced palatability. Fish fed the F18, F11 and F5 diets had significantly lower final body weights than fish fed the F25 diet, with SGR decreased by 5 %, 11 % and 23 %, respectively. The lower growth as FM inclusion in diets decreased was associated with decreased feed intake throughout the trial. In contrast, nutrient utilization was significantly affected in the first phase with increased FCR and decreased PER as FM inclusion decreased. However, there were no significant differences in these parameters in the second phase suggesting that there was metabolic adaptation to the diets. Changes in feed physical texture and/or chemical olfactory attractants possibly reduced the palatability of the diets. Essential fatty acid composition, in particular EPA, DHA and ARA in salmon flesh and liver were not negatively affected by dietary treatment and there was some evidence of increased retention and/or synthesis of LC-PUFA.